(untitled) (Ágora de Heterodoxias, 2021)
A reflection is presented framed in the context of the Self-regulation course at the University of Valparaíso, an institution formed to offer face-to-face classes, which is why it had to abruptly adapt to the remote modality due to the Covid-19 pandemic. The improvisation and compulsory change leads to the impossibility of requiring students to keep the cameras on during synchronous encounters, a situation that generates the problems that we will address here. In this sense, the discussion focused about the difficulties evidenced in evaluating attitudinal competencies through virtual teaching. It was determined that there are four attitudinal contents that can be evaluated remotely and regardless of the use of cameras: participation, teamwork, ethics and responsibility. The conclusions highlight the importance of teachers’ creativity to manage alternatives aimed at maximizing the use of technological resources in evaluation processes.